Menumbuhkan Minat Menabung Sejak Dini Melalui Sosialisasi Pentingnya Menabung di PAUD PGRI Adiwiyata dan Merpati Pos - Miswaty Miswaty; Indri Septianing Ratri; Sukimin Sukimin; Winda Lestari; I Wayan Kartana (Postgraduated Community Service Journal, 2025)
Early-childhood savings socialization activities are one way to increase financial awareness and skills in children. Saving is an important activity that needs to be learned from an early age to develop good financial management habits in the future. However, there are still gaps in the process of teaching children to save, especially at an early age. Therefore, early-childhood savings socialization activities for preschool children are being implemented with the aim of providing students with an understanding and knowledge about saving. These activities are conducted through lectures and savings simulations using piggy banks. It is hoped that children will understand the concept of saving and the benefits of this activity. Survey results indicate that most preschool children understand the meaning and benefits of saving and find the early-childhood savings socialization activities beneficial. Furthermore, teachers and principals responded positively to these activities. Recommendations are given for conducting similar activities annually to help improve students' financial awareness and skills in the future. Early-childhood savings socialization activities for preschool children at PGRI Adiwiyata and Merpati Pos are expected to help change children's mindsets and behaviors regarding financial management, thus forming good savings habits from an early age.